PENGEMBANGAN POTENSI WISATA RELIGI DI KABUPATEN BANJAR KALIMANTAN SELATAN: SEBUAH TINJAUAN LITERATUR - Lola Malihah; Aswan Nazairin; Muhammad Denny Frayoga (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
Religious tourism is a form of special interest tourism that has significant potential to support regional development from economic, social, and cultural perspectives. Banjar Regency, South Kalimantan, is widely recognized as a center of religious activities, characterized by the presence of charismatic Islamic scholars, sacred pilgrimage sites, and well-preserved religious traditions. This study aims to analyze the potential, opportunities, and reinforcing factors for the development of religious tourism in Banjar Regency as a basis for sustainable destination development. This research employs a qualitative approach using a literature review method by examining relevant journal articles, books, and official documents published within the last five years. The findings indicate that religious tourism in Banjar Regency possesses strong potential supported by the symbolic and spiritual values of religious figures, strong social capital within the local community, and visitation patterns that are mass-based and recurring. Furthermore, religious tourism contributes to local economic growth, strengthens social identity, and supports the preservation of local culture. Therefore, the development of religious tourism should be directed toward integrated and sustainable management that upholds religious values, local wisdom, and the principles of sustainable tourism to ensure long-term benefits for both the community and the region..